Purwarupa E-Learning Berbasis Moodle pada One Stop English Course Kudus - Listyorini, Tri; Supriyati, Endang; Arisandi, Bustomi (Dharma: Jurnal Pengabdian Masyarakat, 2022)
The development of learning in a pandemic condition is in the public's attention. In order to prevent the spread of COVID-19, formal and informal schools have started implementing e-learning. Limited face-to-face meetings make learning hampered. Online is one way to keep learning going, through whatsapp groups, zoom, google meet or other platforms. To support online learning, learning at One Stop English (OSE) develops online learning with E-learning using the Moodle platform. With E-learning OSE makes learning easier and more fun, because in E-learning you can share material, do online learning through the platforms that have been provided.